A simple novel approach for detecting blood–brain barrier permeability using GPCR internalization. (27th September 2020) - Csaba, Z.; Vitalis, T.; Charriaut‐Marlangue, C.; Margaill, I.; Coqueran, B.; Leger, P.‐L.; Parente, I.; Jacquens, A.; Titomanlio, L.; Constans, C.; Demene, C.; Santin, M. D.; et al.
Abstract : Aims: Impairment of blood–brain barrier (BBB) is involved in numerous neurological diseases from developmental to aging stages. Reliable imaging of increased BBB permeability is therefore crucial for basic research and preclinical studies. Today, the analysis of extravasation of exogenous dyes is the principal method to study BBB leakage. However, these procedures are challenging to apply in pups and embryos and may appear difficult to interpret. Here we introduce a novel approach based on agonist‐induced internalization of a neuronal G protein‐coupled receptor widely distributed in the mammalian brain, the somatostatin receptor type 2 (SST2). Methods: The clinically approved SST2 agonist octreotide (1 kDa), when injected intraperitoneally does not cross an intact BBB. At sites of BBB permeability, however, OCT extravasates and induces SST2 internalization from the neuronal membrane into perinuclear compartments. This allows an unambiguous localization of increased BBB permeability by classical immunohistochemical procedures using specific antibodies against the receptor. Results: We first validated our approach in sensory circumventricular organs which display permissive vascular permeability. Through SST2 internalization, we next monitored BBB opening induced by magnetic resonance imaging‐guided focused ultrasound in murine cerebral cortex. Finally, we proved that after intraperitoneal agonist injection in pregnant mice, SST2 receptor internalization permits analysis of BBB integrity in embryos during brain development. Conclusions: This approach provides an alternative and simple manner to assess BBB dysfunction and development in different physiological and pathological conditions. Abstract : We introduce a novel approach based on agonist‐induced internalization of a neuronal G protein‐coupled receptor widely distributed in the mammalian brain, the somatostatin receptor type 2 (SST2).This approach provides an alternative and simple manner to assess BBB dysfunction and development in different physiological and pathological conditions.